Pengaruh Motivasi, Kepemimpinan, dan Disiplin Kerja terhadap Kinerja Karyawan Pada PT. X - Chyntia Chyntia; Setia Tjahyanti (Media Bisnis, 2022)
This research was intended to analyze whether Motivation, Leadership, and The Discipline of Work affects employees work on PT. X. The population in this study are permanent employees of PT. X. the population in this study was 146 employees and the sample of this study was 92 employees and the sampling technique used was Purposive Sampling. The method used in this research is a descriptive and causal method. Hypothesis testing in this study uses multiple linear regression analysis method. The data used in this research is a data designed internal covered questionnaires, Based on the results of this study, it is known that motivation and leadership have a significant effect on employee performance. Meanwhile, the Work Discipline doesn’t affect significantly to employee performance on PT. X.